2019
DOI: 10.15244/pjoes/81693
|View full text |Cite
|
Sign up to set email alerts
|

Determining Salinity and Ion Soil Using Satellite Image Processing

Abstract: Arid and semi-arid zones frequently present salinity problems in soils. The agriculture of the municipality of Ahome, Sinaloa has an agricultural region where its soils are characterized by problems of salinity and sodicity-conditions that reduce production. Salinity can be detected by implementing remote sensing techniques; there are ways to enhance the detection of satellite salinity through the use of diverse quantitative models, using the spectral signature of each of the components of the study area throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Several studies have found a positive correlation between NDSI and laboratory data. In studies (Avila Aceves et al 2019;Laiskhanov et al 2016), NDSI provided greater accuracy in the study area, so the obtained values were correlated with soil electrical Our results confirm the correlation and the normalized difference salinity index showed the highest correlation between the results of cations, SAR, ESP (Figure 3 and 4).…”
Section: Resultssupporting
confidence: 77%
“…Several studies have found a positive correlation between NDSI and laboratory data. In studies (Avila Aceves et al 2019;Laiskhanov et al 2016), NDSI provided greater accuracy in the study area, so the obtained values were correlated with soil electrical Our results confirm the correlation and the normalized difference salinity index showed the highest correlation between the results of cations, SAR, ESP (Figure 3 and 4).…”
Section: Resultssupporting
confidence: 77%
“…Remote sensing technology is one of the most effective tools used for soil salinity detection. Researchers from India assessed the feasibility of using remote sensing technology to detect spatio-temporal patterns in soil salinity [14]. They explored different remote sensing satellite systems to delineate the soil salinity boundaries, (e.g.…”
Section: Remote Sensing Approaches For Assessing Soil Salinitymentioning
confidence: 99%
“…They explored different remote sensing satellite systems to delineate the soil salinity boundaries, (e.g. Landsat-7 ETM+ and IRS data) by applying different indices, for example, Salinity Index (SI), Normalized Difference Salinity Index (NDSI), Brightness Index (BI), and Wetness Index (WI) [13]- [14].…”
Section: Remote Sensing Approaches For Assessing Soil Salinitymentioning
confidence: 99%
See 1 more Smart Citation
“…Using spectral response extracted directly from sensors or after the application of spectral transformations, i.e., principal component analysis (PCA) [6,7], tasseled cap transformation [8], and spectral indices [9,10], have given promising results in terms of prediction accuracy. Many scholars emphasize the importance of spectral signature in remote sensing studies as a core concept in this field [11][12][13][14]. Digital soil mapping has been the focus of several research projects operated with different types of remotely sensed data, using statistical or geostatistical methods.…”
Section: Introductionmentioning
confidence: 99%